2018
DOI: 10.3390/cancers11010027
|View full text |Cite
|
Sign up to set email alerts
|

Endolysosomal Ca2+ Signalling and Cancer Hallmarks: Two-Pore Channels on the Move, TRPML1 Lags Behind!

Abstract: The acidic vesicles of the endolysosomal (EL) system are emerging as an intracellular Ca2+ store implicated in the regulation of multiple cellular functions. The EL Ca2+ store releases Ca2+ through a variety of Ca2+-permeable channels, including Transient Receptor Potential (TRP) Mucolipin 1-3 (TRPML1-3) and two-pore channels 1-2 (TPC1-2), whereas EL Ca2+ refilling is sustained by the proton gradient across the EL membrane and/or by the endoplasmic reticulum (ER). EL Ca2+ signals may be either spatially restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 230 publications
(499 reference statements)
2
62
0
Order By: Relevance
“…TPCs are gated by multiple agonists, including nicotinic acid adenine dinucleotide phosphate (NAADP), sphingosine, and the EL phospholipid, phosphatidylinositol 3,5-bisphosphate (Galione 2019). TPCs-mediated Ca 2+ release recruits EL-located Ca 2+sensitive decoders, including calmodulin, synaptotagmin VII, and Arf6 (Faris et al 2018), to regulate vesicular fusion and trafficking (Galione 2019). A screening campaign aiming at repurposing FDA-approved drugs as novel antiviral compounds recently revealed that classical Ca 2+ antagonists blocked Ebola virus and MERS-CoV infections in vitro (Sakurai et al 2015;Gunaratne et al 2018a, b).…”
Section: Repurposing Of Clinically Available Antivirals To Treat Covimentioning
confidence: 99%
“…TPCs are gated by multiple agonists, including nicotinic acid adenine dinucleotide phosphate (NAADP), sphingosine, and the EL phospholipid, phosphatidylinositol 3,5-bisphosphate (Galione 2019). TPCs-mediated Ca 2+ release recruits EL-located Ca 2+sensitive decoders, including calmodulin, synaptotagmin VII, and Arf6 (Faris et al 2018), to regulate vesicular fusion and trafficking (Galione 2019). A screening campaign aiming at repurposing FDA-approved drugs as novel antiviral compounds recently revealed that classical Ca 2+ antagonists blocked Ebola virus and MERS-CoV infections in vitro (Sakurai et al 2015;Gunaratne et al 2018a, b).…”
Section: Repurposing Of Clinically Available Antivirals To Treat Covimentioning
confidence: 99%
“…With the identification of the molecular processes involved in pulmonary carcinogenesis, novel treatments targeting small molecules have emerged with encouraging results. For example, Ca 2+ signaling controls a wide variety of cell functions, such as secretion, gene transcription, cell proliferation and apoptosis [4][5][6]. Alterations of Ca 2+ signaling have emerged to an important factor in cancer progression [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the association of Wnt/β-catenin signaling with the induction of hepatoblastoma, studies have shown that the activation of this signaling also regulates hallmarks of tumor progression including degree of differentiation, invasiveness, metastasis [79]. The down-regulation of disheveled-2, a critical component of Wnt/β-catenin signaling pathway, has been associated with a decrease in the invasiveness of hepatoblastoma [80].…”
Section: Discussionmentioning
confidence: 99%